2023
DOI: 10.4103/sjmms.sjmms_125_23
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Knowledge and Perception of Child Abuse and Neglect in the Eastern Province of Saudi Arabia

Abstract: Background: Child maltreatment is a crucial issue worldwide that has negative consequences for children and their families. Inability to distinguish between traditional corporal punishment and abuse is part of the problem. Objectives: To assess parents’ knowledge and perception of child maltreatment and investigate the factors that influence their awareness. Materials and Methods: This cross-sectional study recruited parents with at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Alsalman et al (2023) [ 8 ] investigated parents' knowledge and perception of child abuse and neglect in the Eastern Province. Only 53% of the participants demonstrated good knowledge of CAN.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Alsalman et al (2023) [ 8 ] investigated parents' knowledge and perception of child abuse and neglect in the Eastern Province. Only 53% of the participants demonstrated good knowledge of CAN.…”
Section: Reviewmentioning
confidence: 99%
“…The studies delving into parental awareness unveiled intriguing insights. Alsalman et al [ 8 ] revealed that while parents perceived CAN as a common problem, a sizable proportion lacked adequate knowledge of the nuances of emotional abuse and neglect. This indicates a vital gap in public awareness that necessitates targeted awareness campaigns, focusing on differentiating between traditional discipline and abusive behavior [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation